Loss of chromosome Y in blood, but not in brain, of suicide completers - Kimura, Atsushi; Hishimoto, Akitoyo; Otsuka, Ikuo; Okazaki, Satoshi; Boku, Shuken; Horai, Tadasu; Izumi, Takeshi; Takahashi, Motonori; Ueno, Yasuhiro; Shirakawa, Osamu; Sora, Ichiro (PloS one, 2018)
Men have a higher rate of completed suicide than women, which suggests that sex chromosome abnormalities may be related to the pathophysiology of suicide. Recent studies have found an aberrant loss of chromosome Y (LOY) in various diseases; however, no study has investigated whether there is an association between LOY and suicide. The purpose of this study was to determine whether LOY occurs in men who completed suicide. Our study consisted of 286 male Japanese subjects comprised of 140 suicide completers without severe physical illness (130 post-mortem samples of peripheral blood and 10 brains) and 146 age-matched control subjects (130 peripheral blood samples from healthy individuals and 16 post-mortem brains). LOY was measured as the chromosome Y/chromosome X ratio of the fluorescent signal of co-amplified short sequences from the Y-X homologous amelogenin genes (AMELY and AMELX). Regression analyses showed that LOY in the blood of suicide completers was significantly more frequent than that found in controls (odds ratio = 3.50, 95% confidence interval = 1.21-10.10), but not in the dorsolateral prefrontal cortex (DLPFC) region of brain. Normal age-dependent LOY in blood was found in healthy controls (r = -0.353, p < 0.001), which was not seen in suicide completers (r = -0.119, p = 0.177). DLPFC tissue had age-dependent LOY (B = -0.002, p = 0.015), which was independent of phenotype. To our knowledge, this is the first study demonstrating that LOY in blood is associated with suicide completion. In addition, our findings are the first to also indicate that age-dependent LOY may occur not only in blood, but also in specific brain regions.